FAPbCl3 Perovskite as Alternative Interfacial Layer for Highly Efficient and Stable Polymer Solar Cells. (27th October 2016) - Wang, Jialin; Peng, Jiajun; Sun, Yong; Liu, Xiaoyu; Chen, Yani; Liang, Ziqi
Abstract : FAPbCl3 perovskite can be utilized as an effective anode interfacial layer (AIL) to conventional poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) for polymer solar cells by benefiting from its high visible transparency, efficient charge extraction, and compatible solution processability. As proof‐of‐concept, such FAPbCl3 AIL based PTB7‐Th:PC71 BM bulk‐heterojunction solar cells exhibit a high power conversion efficiency of 8.75% with good stability.